High Nature Value farming: From indication to conservation. (October 2015) - Strohbach, Michael W.; Kohler, Marina L.; Dauber, Jens; Klimek, Sebastian
Highlights: High Nature Value farming is an established concept in EU conservation policy. Most existing indicators for HNV farming are insufficient for targeting support. Several conservation concepts and policy instruments are relevant to HNV farming. We make suggestions for improving indication and conservation. Abstract: The maintenance of High Nature Value (HNV) farming is a priority for reaching the target of halting biodiversity loss in the European Union by 2020. Nevertheless, since the introduction of the HNV farming concept in the early 1990s and the first call for HNV farmland indicators in 2000, farmland biodiversity has continued to decline in many parts of Europe. The main processes behind this decline are agricultural intensification and abandonment. Past and current agricultural subsidies and conservation measures have mainly failed to safeguard HNV farmland and the respective farming systems. In this paper, we revise current approaches for localizing and characterizing HNV farming, identify shortcomings and describe the next generation of HNV farming indicators; show how HNV farming is related to existing concepts aimed at biodiversity conservation; and provide an overview of EU policy instruments that could help preserve HNV farming. We finish by outlining which steps should be taken so that HNV farming remains a part of our modern agricultural landscape.